2009
DOI: 10.1111/j.1460-9568.2009.06974.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective mental time: the functional architecture of projecting the self to past and future

Abstract: Human experience takes place in the line of mental time (MT) created through 'self-projection' of oneself to different time-points in the past or future. Here we manipulated self-projection in MT not only with respect to one's life events but also with respect to one's faces from different past and future time-points. Behavioural and event-related functional magnetic resonance imaging activity showed three independent effects characterized by (i) similarity between past recollection and future imagination, (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
102
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 55 publications
(224 reference statements)
18
102
2
1
Order By: Relevance
“…The left lateral parietal region that here was related to mental time travel partly overlaps a left angular region shown to be recruited during both past and future thinking (28) and with parietal regions implicated in self-projection in past, present, or future time (29). However, a contribution of the present study is the demonstration that the parietal response was elevated for nonpresent time periods relative to the present.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The left lateral parietal region that here was related to mental time travel partly overlaps a left angular region shown to be recruited during both past and future thinking (28) and with parietal regions implicated in self-projection in past, present, or future time (29). However, a contribution of the present study is the demonstration that the parietal response was elevated for nonpresent time periods relative to the present.…”
Section: Discussioncontrasting
confidence: 52%
“…The task to do (imagining a walk) was identical across conditions-the conditions differed only with regard to subjective time of the imagined activity. Candidate brain regions which hypothetically might code for subjective time include the (medial) prefrontal cortex (16,19), hippocampus (8), and parietal cortex (28,29).…”
mentioning
confidence: 99%
“…Another line of evidence marshalled in support of an episodic/FMTT connection is that these two phenomena share many neural substrates (primarily in the medial temporal lobes: e.g., Addis, Wong, & Schacter, 2007;Arzy, Collette, Ionata, Fornari, & Blanke, 2009;Race et al, 2011;Verfaellie, Race, & Keane, 2013). This apparently confers a degree of respectability on the hypothesis that episodic memory (somehow) is involved in FMTT.…”
Section: Conclusion: the Relation Between Episodic Memory And Fmtt Rmentioning
confidence: 99%
“…2 Theoretical and investigative attention remains largely trained on the contributions of episodic memory to future-oriented thought and behavior-despite increasing evidence for the role played by a range of recently evolved and late-developing cognitive capacities (e.g., systems of knowledge, executive function, scene construction, temporal self-projection, imagination; e.g., Arzy, Collette, Ionata, Fornari, & Blanke, 2009;Craver, Kwan, Steindam, & Rosenbaum, 2014;Irish, Addis, Hodges, & Piguet, 2012;Irish & Piguet, 2013;Kwan et al, 2012;Maguire & Mullally, 2013;Manning, Denkova, & Unterberger, 2013;Mullaley, Vargha-Khadem, & Maguire, 2014;Schacter et al, 2012, Suddendorf, 2010Zeithamova, Schlichting, & Preston, 2012).…”
Section: The Role Of Episodic Memory In Contemporary Treatments Of Fmttmentioning
confidence: 99%
“…Similar sentiments are voiced by de Vito, Gamboz, Brandimonte, Barone, Amboni, and Della Salla (2012), who argue that executive function plays a crucial role in Parkinson's patients' performance on future thinking tasks. Arzy, Collette, Ionata, Fornari, and Blanke (2009) have shown that brain areas associated with mental imagery must be taken into account for some forms of FMTT. These data are telling us that a full appreciation of FMTT requires that we recognize that neurocognitive mechanisms other than memory (and the subjective temporalities they entail) play an important role in our ability to orient toward the future (for discussion, see Klein, 2013a).…”
Section: Beyond Memorymentioning
confidence: 99%